Frequency of Midline Diastema in patients reported To OPD of Bacha Khan Medical College Mardan - Bibi Maryam, Javaria Imtiaz, Umar Nasir, Shaheen, Aqsa Mumtaz, Nauman Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A space between adjacent central incisor teeth is termed "diastema or diastemata". Midline diastema in mixed dentition is a great center of concern for parents as well as their children, therefore, determining the time of closure of midline diastema is essential for clinical practice in Orthodontic and the study was aimed to determine the frequency of midline diastema in both maxillary and mandibular arches in patients. Material and Method: The current study was carried out at Bacha Khan Medical College Mardan, Khyber Pukhtoon Khwa to determine the frequency of midline diastema in both maxillary and mandibular arches in patients for which a total of 200 responders have examined 100 responders were males while 100 were female. Results: The frequency of Midline diastema was 12%, out of 200 hundred in which Maxillary midline diastema was 5% and Mandibular midline diastema was 5.5% and both the arches were found to be 1.5% in females. Conclusion: The finding of the current study is that the population of Khyber Pukhtunkhwa has several Midline diastemata affecting their esthetic. A similar study to find out the etiology of Midline diastema is suggested which requires a large sample size.